2009
DOI: 10.1007/s10800-009-9879-1
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured bimetallic alloys prepared via mechanochemical synthesis as PEMFC electrocatalysts for automotive applications

Abstract: Pt-Co alloys prepared by high energy ball milling synthesis were tested as electrocatalysts for hydrogen fueled Polymer Electrolyte Membrane Fuel Cells (PEMFC). In the present contribution we report on the first results regarding the electrochemical behaviour of two samples of Pt-Co alloys. One sample contains 20 wt.% alloy Pt:Co in the molar ratio 0.25:0.75 and C 80 wt.% and the second one Pt:Co in the molar ratio 0.75:0.25 and C 80 wt.%. The electrochemically active surface (EAS) was determined by cyclic vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Metal co-deposition is relatively easy with the appropriate conditions, but the formation of an alloy usually requires subsequent thermal treatments [13,20,21,23]. Interestingly, it has been found that energy-intensive thermal steps can be overcome by longer milling times [11,14,24], even if this can lead to the contamination of the catalyst by the milling media. Regarding catalytic properties, the improvement of performance in terms of the activity, stability, and/or selectivity of bimetallic milled catalysts compared to analogous formulations obtained via other synthesis methods is widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Metal co-deposition is relatively easy with the appropriate conditions, but the formation of an alloy usually requires subsequent thermal treatments [13,20,21,23]. Interestingly, it has been found that energy-intensive thermal steps can be overcome by longer milling times [11,14,24], even if this can lead to the contamination of the catalyst by the milling media. Regarding catalytic properties, the improvement of performance in terms of the activity, stability, and/or selectivity of bimetallic milled catalysts compared to analogous formulations obtained via other synthesis methods is widely reported.…”
Section: Introductionmentioning
confidence: 99%